Development and validation of a prognostic model to predict the prognosis of patients who underwent chemotherapy and resection of pancreatic adenocarcinoma: a large international population-based cohort study - Huang, Lei; Balavarca, Yesilda; Schrotz-King, Petra; Brenner, Hermann (BMC medicine, 2019)
Pancreatic cancer (PaC) remains extremely lethal worldwide even after resection. PaC resection rates are low, making prognostic studies in resected PaC difficult. This large international population-based study aimed at exploring factors associated with survival in patients with resected TNM stage I-II PaC receiving chemotherapy and at developing and internationally validating a survival-predicting model.
Gesehen am 08.04.2019